Increasing Surface Hardness and Corrosion Resistance of AISI 410 Stainless Steel by Forming a Diamond-Like Carbon Thin Film - Agung Setyo Darmawan, Agung Setyo Darmawan; Agus Yulianto, Agus Yulianto; Bambang Waluyo Febriantoko, Bambang Waluyo Febriantoko; Bibit Sugito, Bibit Sugito; Suprapto, Suprapto; Tjipto Sujitno, Tjipto Sujitno; Turnad Lenggo Ginta, Turnad Lenggo Ginta; Abdul Hamid, Abdul Hamid (2024)
AISI 410 stainless steel plays an important role in many engineering fields. The annealing process of this material will increase toughness. But this process will also reduce the hardness of the material. Plasma chemical vapor deposition was carried out to increase the surface hardness and corrosion resistance of AISI 410 stainless steel. In this study, the raw material was tested for metallography, hardness, and corrosion resistance. Then an annealing process was carried out on the raw material. The annealed material was also observed for metallography, hardness, and corrosion resistance. Furthermore, on the annealed material, the plasma chemical vapor deposition process was carried out with pressure variations of 1.0, 1.2, 1.4, and 1.6 mbar. Next, the material was tested for metallography with a scanning electron microscope to measure the layer thickness. The formation of diamond-like carbon was confirmed by the Raman Spectroscopy test. Annealed followed by plasma chemical vapor deposition processed AISI 410 stainless steel also tested for hardness and corrosion. The results showed that the annealed AISI 410 stainless steel underwent a phase change from martensite and retained austenite to ferrite and pearlite. The annealed raw material experienced a decrease in hardness and corrosion rate. After the annealed material was processed by plasma chemical vapor deposition, The thickness of the surface layer increased with increasing pressure. Along with that, the hardness and corrosion resistance increased.